Comparison of Formulation Methods to Produce Nano-Chitosan as Inhibitor Agent for Bacterial Growth - Nugraheni, Prihati Sih; Soeriyadi, Alexander H.; Ustadi, Ustadi; Sediawan, Wahyudi Budi; Budhijanto, Wiratni (Journal of Engineering and Technological Sciences, 2019)
Chitosan is known as an antibacterial agent. The effective surface area ratio of chitosan can be increased by modification into nanoparticles. Nano-chitosan can be prepared with several simple methods, i.e. precipitation, ionic gelation, or the polyelectrolyte complex method. This study compared these three methods in terms of the targeted product characteristics, i.e. stability of the average nanoparticle size as well as the colloidal dispersion, and the antibacterial characteristics. All three methods resulted in nanoparticle formation, but in the precipitation method significant zeta potential reduction was observed due to the presence of negative ions from the alkali that neutralized the chitosan amine group. The ionic gelation method yielded higher zeta potential and higher inhibition of bacterial growth than those yielded by the polyelectrolyte complex method. Ionic gelation and the polyelectrolyte complex method resulted in much better colloidal dispersion stability than the precipitation method, where a significant particle size increase was observed after one week of storage. This result indicates that both ionic gelation and the polyelectrolyte complex method can be used for forming nano-chitosan for the purpose of food preservation. However, for fishery products it is advisable to use the polyelectrolyte complex method because the TPP usually used in ionic gelation is not allowed to be applied to fish.